2023
DOI: 10.1039/d2se00055e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle assessment of corn stover conversion by decentralized biomass pyrolysis-electrocatalytic hydrogenation versus ethanol fermentation

Abstract: Quantification of environmental impacts through life cycle assessment is essential when evaluating bioenergy systems as potential replacements for fossil-based energy systems. Bioenergy systems employing localized fast pyrolysis combined with electrocatalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The costs of transportation were added to the reported values of each feedstock. The average trucking distance was calculated, as depicted in Figure . Rectangular coordinates were assumed because plots of land and the orientation of roads are generally rectangular.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The costs of transportation were added to the reported values of each feedstock. The average trucking distance was calculated, as depicted in Figure . Rectangular coordinates were assumed because plots of land and the orientation of roads are generally rectangular.…”
Section: Methodsmentioning
confidence: 99%
“…The average trucking distance was calculated, as depicted in Figure 5. 54 Rectangular coordinates were assumed because plots of land and the orientation of roads are generally rectangular. The refinery was assumed to occupy the center of a 2.01 × 2.01 km 2 area not designated for cultivation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Published assessments of GHG mitigation with biofuels have focused primarily on displaced fossil fuel emissions rather than CO 2 capture. 21,22 It has been suggested that in time the value of biomass energy systems for photosynthetic carbon removal may exceed that for energy supply. 23,24 Studies have recently begun to leverage carbon capture and storage (CCS) technologies to enable net negative life-cycle emissions for biofuel production.…”
Section: Introductionmentioning
confidence: 99%